2017
DOI: 10.4172/2329-9029.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Asiaticoside by Using RP-HPLC and FAME Analysis of Medicinally Important Plant Centella asiatica

Abstract: Due to the presence of several bioactive compounds, Centella asiatica (L.) is used in traditional medicine for the treatment of various ailments. This usage of plant and its products created a huge demand which required an alternative method of its commercial production so that the loss of natural plant and its genetic pool can be prevented. A different investigation using biotechnological methods provided a wealth of information to enhance the biomass as well as different bioactive compounds. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Hence ICME can play a role in many diseases in which oxidative stress is a major factor in its pathogenesis as the case in AD. This assumption is supported by other studies that showed the potential of some plants in AD based on their antioxidant and free radicle scavenging activities as Withanamides, Bacopa monnieri and Centella asiatica plants ( Limpeanchob et al., 2008 ; Jayaprakasam et al., 2010 ; Roy et al., 2017 ).…”
Section: Discussionsupporting
confidence: 73%
“…Hence ICME can play a role in many diseases in which oxidative stress is a major factor in its pathogenesis as the case in AD. This assumption is supported by other studies that showed the potential of some plants in AD based on their antioxidant and free radicle scavenging activities as Withanamides, Bacopa monnieri and Centella asiatica plants ( Limpeanchob et al., 2008 ; Jayaprakasam et al., 2010 ; Roy et al., 2017 ).…”
Section: Discussionsupporting
confidence: 73%
“…Thus it can be concluded that this plant is a good source of fatty acids and can be used in cholesterol-lowering diets. Similar study has been conducted by Roy et al [15]…”
Section: Fatty Acid Methyl Ester (Fame) Production and Analysissupporting
confidence: 86%
“…23 Asiatic acid and asiaticoside showed reduce hydrogen peroxide-induced cell death, decline concentration of free radicals, and β-amyloid cell death inhibition in vitro which suggested possible role in Alzheimer's disease treatment and β-amyloid toxicity prevention. [24][25][26] Extracts of Centella asiatica reversed the β-amyloid pathology in mice brains and modulated oxidative stress response components. 27 It is an important plants for nerve and brain cells and considers being capable of enhancing intellect, memory and longevity.…”
Section: Centella Asiatica (Gotu Kola)mentioning
confidence: 99%